THE INFLUENCE OF GADGET USE ON SPEECH DELAY IN TODDLERS (AGES 1-5) - Sitohang, Devita Pingkan; Damanik, Bernieke Anggita Ristia (Sindoro: Cendikia Pendidikan, 2025)
This study examines the influence of gadget use on speech delay in toddlers aged 1 to 5 years. With the increasing accessibility of gadgets, attention to children's language development has become increasingly important. The methodology includes surveys and observations of 4 parents. The findings indicate that children exposed to excessive gadget use experience delays in speech development compared to those with limited gadget exposure. This research concludes that uncontrolled gadget use can negatively impact children's speaking abilities. Therefore, it is recommended that parents limit gadget usage and engage more in verbal interactions with their children.